2008
DOI: 10.1136/hrt.2007.134783
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve calcification: basic science to clinical practice

Abstract: Calcific aortic valve stenosis is the result of regulated cell processes. The histological hallmarks are inflammation and a remodelling of the extracellular matrix leading to bone formation. In the last 15 years the view has changed from it being an unmodifiable degenerative disease to an active biological process regulated by highly conserved ubiquitous cellular pathways. Many mechanisms and risk factors are the same as in atherosclerosis. Thus, statins and angiotensin II antagonists seemed promising treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 110 publications
1
82
0
2
Order By: Relevance
“…Calcific aortic stenosis (AS) is a progressive disease that has, until recently, been considered a degenerative and unmodifiable process induced by long-lasting mechanical stress on the valve structures [1][2][3]. However, histopathological studies have now demonstrated that the pathogenesis of calcific AS is an active process, sharing a number of similarities with atherosclerosis [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Calcific aortic stenosis (AS) is a progressive disease that has, until recently, been considered a degenerative and unmodifiable process induced by long-lasting mechanical stress on the valve structures [1][2][3]. However, histopathological studies have now demonstrated that the pathogenesis of calcific AS is an active process, sharing a number of similarities with atherosclerosis [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation, lipid infiltration, dystrophic calcification, ossification, platelet activation and endothelial dysfunction have been observed in both diseases. Early in the development of AS, active microscopic areas of calcification are seen colocalizing in areas of lipoprotein accumulation and infiltration of inflammatory cells [1,[3][4][5]. As the disease progresses, there is active bone formation involving cells with chondrocytic and ⁄ or osteoblastic characteristics capable of phenotypic differentiation and spontaneous calcification [3,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of these patients had severe AVS. Recently, Akat et al (2009) reported that foci of micro-calcification have been observed in the early stage of CAVD (AVSc or mild AVS). In the Cardiovascular Health Study, elevated phosphate levels, but not calcium, parathyroid hormone, or 25-OHD levels in serum, were associated with AVSc in a community-based cohort of older adults (Linefsky et al, 2011).…”
Section: Relation Between Mineral Metabolism Disturbance and Cavdmentioning
confidence: 99%
“…DOI: 10.21883/PJTF.2017.09. 44580.16533 Природа минеральных (кальцинированных) образований на сосуди-стых стенках, будучи причиной трети сердечно-сосудистых болезней [1], продолжает привлекать неослабевающее внимание исследователей. Среди используемых при этом методов важное место принадлежит ИК-спектроскопии [2,3].…”
Section: поступило в редакцию 24 октября 2016 гunclassified